Comparative Study of Ziehl-Neelsen Stain versus Fluorescent Microscopy in Diagnosis of Tuberculous Lymphadenitis on FNAC at A Tertiary Care Centre - Dr. Dnyaneshwar Shivajirao Jadhav; Dr.Vaibhav Vilas Deshmukh; Dr. Nikhileshwar Haldhar Mahato; Dr. Arvindbhai Govindbhai Valand (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Worldwide, TB is one of the top 10 causes of death and the leading cause from a single infectious agent. Lymph nodes tuberculosis is considered the most common form of extrapulmonary tuberculosis and most common cause of lymphadenopathy in developing countries like India.Conventional Ziehl-Neelsen (ZN) method & Fluorescent microscopy (FM) plays an important role for detection of Acid fast bacilli (AFB).Objectives: This study is an attempt to find out cost effective, rapid and sensitive technique for early diagnosis of tuberculous lymphadenitis. To study incidence, age, sex and site wise distribution of tuberculous lymphadenitis in this area.Material Methods: The prospective observational study was carried out in the Department of Pathology, S.R.T.R. Govt. Medical College, Ambajogai in year 2017. All 247 aspirated samples from Lymph node swellings were subjected to ZN stain, Fluorescent stain, MGG & PAP stain and 52 cases of tuberculous lymphadenitis were subjected for further analysis,Results: Out of 247 samples aspirated from lymph node lesions 52 were of tuberculous lymphadenitis (21.05%). For tuberculous lymphadenitis, age ranged from 7 months to 77 years. Female predominance was noted with Female to male ratio 1.17:1. Half of the cases were in the range of 21-40 years of age. Cervical region was the commonest siteinvolved with 51.92%. Of 52 aspirates, smear positivity of AFB on ZN stain method was 78.84%, while positivity of Auramine fluorescent stain method was 90.38%.Conclusion: In developing countries with high prevalence of tuberculosis, Fine needle aspiration cytology (FNAC) coupled with fluorescent stain & ZN stain could distinctively improve diagnosis of tuberculous lymphadenitis in patients presenting with superficial lymphadenopathy.